Sphere-Formation Assay: Three-Dimensional in vitro Culturing of Prostate Cancer Stem/Progenitor Sphere-Forming Cells - Bahmad, Hisham F.; Cheaito, Katia; Chalhoub, Reda M.; Hadadeh, Ola; Monzer, Alissar; Ballout, Farah; El-Hajj, Albert; Mukherji, Deborah; Liu, Yen-Nien; Daoud, Georges; Abou-Kheir, Wassim (Frontiers in Oncology, 2018)
Cancer Stem Cells (CSCs) are a sub-population of cells, identified in most tumors, responsible for the initiation, recurrence, metastatic potential and resistance of different malignancies. In prostate cancer (PCa), CSCs were identified and thought to be responsible for the generation of the lethal subtype, commonly known as Castration-Resistant Prostate Cancer (CRPC). In vitro models to investigate the properties of CSCs in PCa are highly required. Sphere-formation assay is an in vitro method commonly used to identify CSCs and study their properties. Here, we report the detailed methodology on how to generate and propagate spheres from PCa cell lines and from murine prostate tissue. This model is based on the ability of stem cells to grow in non-adherent serum-free gel matrix. We also describe how to use these spheres in histological and immuno-fluorescent staining assays to assess the differentiation potential of the CSCs. Our results show the sphere-formation Assay (SFA) as a reliable in vitro assay to assess the presence and self-renewal ability of CSCs in different PCa models. This platform presents a useful tool to evaluate the effect of conventional or novel agents on the initiation and self-renewing properties of different tumors. The effects can be directly evaluated through assessment of the sphere-forming efficiency (SFE) over five generations or other downstream assays such as immuno-histochemical analysis of the generated spheres.